Tahlîlu al Akhta’ fi Mahậrah al Kalậm bi al-Lughah al-Arabîyah li Tullậbi Ma’hadi Sirậj at-Thậlibîn al-Islậmiy - Kurniawati, Ela; Ni'mah, Mamluatun; Sofa, Ainur Rofiq (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research is motivated by the issues related to the low ability of students in pronouncing letters, words, or sentences in Arabic, especially for beginner learners, to prevent future errors that may hinder the learning process. This study aims to analyze students' errors in reading Arabic texts from a phonological perspective. It is a qualitative research with a descriptive research design. The results of this research are as follows. Firstly, the phonological error forms in Arabic speaking skills among students of the Siraaj Al-Thalibin Islamic boarding school include errors in throat consonant groups (الحلق) and tongue groups (اللسان); vowel errors such as vowel deletion, vowel substitution, and long-short vowel errors; diphthong errors; double consonant errors (الشد); and assimilation errors (ال). Secondly, the factors causing errors in Arabic language speaking skills include linguistic and non-linguistic factors. Non-linguistic factors such as low interest and motivation in language learning, and lack of application of the Arabic language.